Alginate-Derivative Encapsulated Carbon Coated Manganese-Ferrite Nanodots for Multimodal Medical Imaging - Pemula Gowtham; Koyeli Girigoswami; Pragya Pallavi; Karthick Harini; Ilangovan Gurubharath; Agnishwar Girigoswami (Pharmaceutics, 2022)
Carbon-decorated ferrite nanodots (MNF@Cs) have been enhanced with superparamagnetism and higher fluorescence quantum yield by encapsulation with an alginate derivative to create a cost-effective and less toxic multimodal contrast agent for replacing the conventional heavy metal Gd-containing contrast agent used in MR imaging. The novel surface-engineered particles (MNF@C-OSAs), devoid of labels, can simultaneously provide both longitudinal and transverse relaxation-based magnetic resonance imaging (MRI) and fluorescence emission. According to the findings of in vitro studies, the calculated molar relaxivities and the molar radiant efficiencies are indicative of the multimodal efficacy of MNF@C-OSA as compared with MNF@C particles and conventional contrast agents used in medical imaging. MNF@C-OSAs were shown to be significantly biocompatible and negligibly toxic when assessed against A549 cells and zebrafish embryos, indicating their potential for use as theranostic agents.